Promoting healthy eating, active play and sustainability consciousness in early childhood curricula, addressing the Ben10™ problem: a randomised control trial - Skouteris, Helen (BioMed Central, 2014)
BACKGROUND: This paper details the research protocol for a study funded by the Australian Research Council. An integrated approach towards helping young children respond to the significant pressures of ‘360 degree marketing’ on their food choices, levels of active play, and sustainability consciousness via the early childhood curriculum is lacking. The overall goal of this study is to evaluate the efficacy of curriculum interventions that educators design when using a pedagogical communication strategy on children’s knowledge about healthy eating, active play and the sustainability consequences of their toy food and toy selections. METHODS/DESIGN: This cluster-randomised trial will be conducted with 300, 4 to 5 year-old children attending pre-school. Early childhood educators will develop a curriculum intervention using a pedagogical communication strategy that integrates content knowledge about healthy eating, active play and sustainability consciousness and deliver this to their pre-school class. Children will be interviewed about their knowledge of healthy eating, active play and the sustainability consequences of their food and toy selections. Parents will complete an Eating and Physical Activity Questionnaire rating their children’s food preferences, digital media viewing and physical activity habits. All measures will be administered at baseline, the end of the intervention and 6 months post intervention. Informed consent will be obtained from all parents and the pre-school classes will be allocated randomly to the intervention or wait-list control group. DISCUSSION: This study is the first to utilise an integrated pedagogical communication strategy developed specifically for early childhood educators focusing on children’s healthy eating, active play, and sustainability consciousness. The significance of the early childhood period, for young children’s learning about healthy eating, active play and sustainability, is now unquestioned. The specific teaching and learning practices used by early childhood educators, as part of the intervention program, will incorporate a sociocultural perspective on learning; this perspective emphasises building on the play interests of children, that are experienced within the family and home context, as a basis for curriculum provision. TRIAL REGISTRATION: Australian New Zealand Clinical Trials Registry ACTRN12614000363684: Date registered: 07/04/2014